An Analysis of Patient and Fracture Characteristics and Clinical Outcomes in Patients With Hyperostotic Spine Fractures. Issue 8 (December 2020) - Bernstein, David N.; McCalla, Daren J.; Molinari, Robert W.; Rubery, Paul T.; Menga, Emmanuel N.; Mesfin, Addisu
Study Design: Retrospective study. Objective: To evaluate outcomes and complications following operative and nonoperative management of hyperostotic spine fractures. Methods: Patients presenting between 2008 and 2017 to a single level 1 trauma center with hyperostotic spine fractures had their information and fracture characteristics reviewed. Bivariate analyses were conducted to compare patients across a number of characteristics and outcomes. Multivariate logistic regression models for complication and mortality were done in a stepwise fashion. Results: Sixty-five ankylosing spondylitis (AS) or diffuse idiopathic skeletal hyperostosis (DISH) patients with a spine fracture met our inclusion criteria. DISH was slightly more prevalent (55% vs 45%). Overall delayed diagnosis, reoperation, mortality (at 1 year), and complication rates were high at 32%, 13%, 23%, and 57%, respectively. In multivariate logistic regression models, patients undergoing operative management had significantly increased odds of having a complication (odds ratio [OR] = 23.03, 95% confidence interval [CI] = 2.24-236.45, P = .008), while increasing age was associated with increased odds of death (OR = 1.18, 95% CI = 1.06-1.31, P = .003). Conclusions: Patients with AS or DISH who fracture their spine are at high risk of complication and death. However, neither operative nor nonoperative treatment increases the odds of mortality. This study helps add to a growing, but still limited, body of literature on the characteristics of patients with spine fractures in the setting of AS or DISH.